AB1223 Evaluation of the factors affecting colchicum resistance, treatment adherence and accuracy of diagnosis in colchicum resistant familial mediterranean fever (FMF) patients. (23rd January 2014) - Cetin, G.Y.; Sayarlioglu, H.; Orhan, O.; Pehlivan, Y.; Balkarli, A.; Sagliker, H.S.; Kisacik, B.; Onat, A.M.; Cobankara, V.; Sayarlioglu, M.
Abstract : Objectives: This study attempts to investigate diagnosis accuracy, treatment adherence, and potential reasons including demography, clinic, socio-economic status, laboratory markers, and psychiatric dynamics that may cause colchicum resistancein FMF patients. Methods: 59 FMF patients (38F/21M) prospectively assigned to the study from three different centers. Colchicum resistance (CR) defined as two or more attacks in 6 months period along with the standard therapy of 2mg/day. Of the total patients, 18 patients (9F/9M) enrolled into CR group, and 41 patients enrolled into control group (12M/29F). Patients with less then two attacks in six months treatment period assigned into control group. All patients requestioned according to the Livneh diagnosis criteria of FMF. Treatment adherence evaluated using demographic, clinical, laboratory and socio-economic findings, and Beck's depression scale scores with a standardized protocol. Results: There was notastatistically significant difference between the groups concerningthe demographic values. The FMFdiagnosis of all patients in both groups validatedwith Livneh diagnosis criteria, and all FMF diagnosis were correct. Diseases onset age was significantly lower in CR group (12 and 17, p=0.03). Althoughdiseases duration was longer in CR group (p=0, 01), there was not a statisticallysignificant difference concerning thediagnosis ageand diseases onset age. Concerning the attack features ofthe two groups, ileumpain, and leg pain due to exercises were significantly higher in CR group (83% and 51% p=0, 02, 88% and 60% p=0, 04 respectively). Frequency of hematuria and proteinuria during the FMF attacks were gradually higher in CR group (p=0, 006). There was statistically significant difference concerning the treatmentadherence (p=0, 01). Beck's depression scoresover 17 points of the CR groupwere predominantly higher than the controls (p<0, 001). Conclusions: One of the earliest studies on this topic revealed that CR patients had inferior socio-economic andeducation status (1). Morover, previous studies demonstratethat presence of depression in FMF patients is more common (2) and frequency of attacks in CR patients relatively diminished followingthe depression therapy (3). Colchicum resistant patients need to be questioned for accurate use of drugs and depression. References: Lidar M, Scherrmann JM, Shinar Y and et al. Colchicine non-responsiveness in familial Mediterranean fever: clinical, genetic, pharmacokinetic, and socioeconomic characterization. Semin. Arthr Rhe. 2004 Feb;33(4):273-82 Deger SM, Ozturk MA, Demirag MD et al. Health-related quality of life and its associations with mood condition in familial Mediterranean fever patients. Rhe Int (2011) 31:623–62 Onat AM, Ozturk MA, Ozcakar L et al. Selective Seratonin Reuptake Inhibitors Reduce the Attack Frequency in Familial Mediterranean fever. Tohoku J.Exp.Med, 2007, 211, 9-14 Disclosure of Interest: None Declared